Egypt Note : Selected Issues and Options for the Education Sector - Wodon, Quentin T.; Evans, Brooks; Male, Chata; Onagoruwa, Adenike; Savadogo, Aboudrahyme; Yedan, Ali (World Bank, Washington, DC, 2017)
This note provides a diagnostic of issues faced by the pre-tertiary education sector in the areas of schooling, learning, education and labor market earnings, and education spending.Acknowledging the Ministry of Education and Technical Education (MOETE) strategy for the sector and the Vision 2030, the note also discusses challenges in six areas: (1) Early childhood education; (2) Teacher policies; (3) Student assessment; (4) TVET/skills development; (5) School autonomy/accountability; and (6) curriculum, ICT, and materials.